Bortezomib, thalidomide and dexamethasone, with or without cyclophosphamide, for patients with previously untreated multiple myeloma: 5‐year follow‐up. (7th July 2015) - Ludwig, Heinz; Greil, Richard; Masszi, Tamas; Spicka, Ivan; Shpilberg, Ofer; Hajek, Roman; Dmoszynska, Anna; Paiva, Bruno; Vidriales, María‐Belén; Esteves, Graca; Stoppa, Anne Marie; Robinson, Don; et al.
Summary This follow‐up extension of a randomised phase II study assessed differences in long‐term outcomes between bortezomib‐thalidomide‐dexamethasone (VTD) and VTD‐cyclophosphamide (VTDC) induction therapy in multiple myeloma. Newly diagnosed patients (n = 98) were randomised 1:1 to intravenous bortezomib (1·3 mg/m2; days 1, 4, 8, 11), thalidomide (100 mg; days 1–21), and dexamethasone (40 mg; days 1–4, 9–12), with/without cyclophosphamide (400 mg/m2; days 1, 8), for four 21‐day cycles before stem‐cell mobilisation/transplantation. After a median follow‐up of 64·8 months, median time‐to‐next therapy was 51·8 and 47·9 months with VTD and VTDC, respectively. Type of subsequent therapy was similar in both arms. After adjusting for asymmetric censoring, median time to progression was not significantly different between VTD and VTDC [35·7 vs. 34·5 months; Hazard ratio (HR) 1·26, 95% confidence interval: 0·76–2·09; P = 0·370]. Five‐year survival was 69·1% and 65·3% with VTD and VTDC, respectively. When analysed by minimal residual disease (MRD) status, overall survival was longer in MRD‐negative versus MRD‐positive patients with bone marrow‐confirmed complete response (HR 3·66, P = 0·0318). VTD induction followed by transplantation provides long‐term disease control and, consistent with the primary analysis, there is no additional benefit from adding cyclophosphamide. This study was registered at ClinicalTrials.gov (NCT00531453).